ANALYTICAL METHOD DEVELOPMENT AND VALIDATION STUDIES OF TICAGRELOR TABLETS BY RP-HPLC - Tabassum, K.; Sarvesh, R. (International Journal of Applied Pharmaceutics, 2017)
Objective: The present study was conducted to develop a simple and precise analytical method for the estimation of ticagrelor in tablet formulation. Methods: Reverse Phase HPLC was used for method development and validation studies of ticagrelor. The optimum chromatographic conditions comprised of C18 column (Kromasil, 250Ã—4.6 mm, 5 Âµ) as the stationary phase and aqueous buffer (containing 0.5 ml formic acid and triethylamine each in water) and acetonitrile in the ratio of 50:50 v/v as the mobile phase. The flow rate was 1.3 ml/min with detection at 256 nm and a run time of 6 min. Forced degradation studies were conducted and the isocratic mode was modified to a gradient mode to make the method stability indicating in nature. Results: The retention time of ticagrelor was 3.372 min. The linearity studies indicated that the range of the developed method was 20-90 ppm with a correlation coefficient of 0.9956. The method was specific with a percent mean recovery was found to be 99.93%.. The % RSD in the precision studies was 0.069. The validated method was applied to conduct the assay of ticagrelor in tablets and the with a percent mean recovery of 99.82%. The modified method was capable of resolving 13 related substances from the ticagrelor peak in the forced degradation studies. Conclusion: The developed and validated RP-HPLC isocratic method was simple, accurate and precise as per the ICH guidelines. It was suitable for the analysis of ticagrelor in bulk and tablet formulation. The modified gradient method can be used to resolve the in-process impurities and related substances and can be directly applied to liquid chromatography hyphenated with mass spectroscopy (LC/MS) studies with minor modifications for identification of related substances.